The development of scales to measure childhood cancer survivors' readiness for transition to long‐term follow‐up care as adults. (22nd July 2014) - Klassen, Anne F.; Rosenberg‐Yunger, Zahava R.S.; D'Agostino, Norma M.; Cano, Stefan J.; Barr, Ronald; Syed, Iqra; Granek, Leeat; Greenberg, Mark L.; Dix, David; Nathan, Paul C.
Abstract: Purpose: To develop and validate scales to measure constructs that survivors of childhood cancer report as barriers and/or facilitators to the process of transitioning from paediatric to adult‐oriented long‐term follow‐up (LTFU) care. Methods: Qualitative interviews provided a dataset that were used to develop items for three new scales that measure cancer worry, self‐management skills and expectations about adult care. These scales were field‐tested in a sample of 250 survivors aged 15–26 years recruited from three Canadian hospitals between July 2011 and January 2012. Rasch Measurement Theory (RMT) analysis was used to identify the items that represent the best indicators of each scale using tests of validity (i.e. thresholds for item response options, item fit statistics, item locations, differential item function) and reliability (Person Separation Index). Traditional psychometric tests of measurement performance were also conducted. Results: RMT led to the refinement of a 6‐item Cancer Worry scale (focused on worry about cancer‐related issues such as late effects), a 15‐item Self‐Management Skills scale (focused on skills an adolescent needs to acquire to manage their own health care), and a 12‐item Expectations scale (about the nature of adult LTFU care). Our study provides preliminary evidence about the reliability and validity of these new scales (e.g. Person Separation Index ≥ 0.81; Cronbach's α ≥ 0.81; test–retest reliability ≥ 0.85). Conclusion: There is limited knowledge about the transition experience of childhood cancer survivors. These scales can be used to investigate barriers survivors face in the process of transition from paediatric to adult care.